Non-Alcoholic Fatty Liver Disease (NAFLD), characterization, diagnosis and treatment (Research, Society and Development, 2023)
Introduction: Non-Alcoholic Fatty Liver Disease (NAFLD) is characterized by the accumulation of fat in the liver and can progress to fibrosis and necroinflammatory changes. It is a multifactorial and complex pathology associated with ethnicity, gender, age, metabolic and endocrine conditions, drug intoxication, among others. Objective: Given the conditions related to the condition, this narrative review aimed to characterize the pathology, its implications, diagnostic strategies and main procedures with an emphasis on nutrition. Material and methods: For this purpose, 44 scientific articles published between 2015 and 2023 were selected, in the main databases: Lilacs, Pubmed, Scielo and Google Scholar. Results and discussion: NAFLD is directly associated with insulin resistance and obesity. Although biopsy is considered the gold standard in diagnosing the disease, biochemical investigation and imaging are used more frequently. Conclusion: NAFLD treatment is based on lifestyle modifications, considering encouraging physical activity, improving the qualitative and quantitative aspects of the diet and including phytochemicals and bioactive compounds in the patient's dietary routine.